Bismuth Ions Selective Fluorescent Chemosensor Based on Rhodamine-B - Yu, Lianwei; Tian, Jianfei; Tian, Fuli (Asian Journal of Chemistry, 2015)
A new rhodamine-based compound (L1) has been synthesized and applied as an “off-on” chemosensor for Bi3+. The complexation behaviour of chemosensor with different metal ions including Bi3+ ions in EtOH/H2O (4:1, v/v) was studied on UV-visible absorption spectra and fluorescent spectra. Results showed that the chemosensor (L1) is highly selective for Bi3+ over other cations such as Hg2+, Fe2+, Mn2+ and Ca2+. This selectivity can be attributed to the photoinduced electron transfer mechanism (PET) of the sensor in the presence of Bi3+. The complex solution (L1-Bi3+) exhibited reversibility with EDTA.